2017
DOI: 10.1002/cbin.10833
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and free fatty acids induce endothelial progenitor cell senescence via PGC‐1α/SIRT1 signaling pathway

Abstract: The objective of the research was to investigate the function of endothelial progenitor cells (EPCs) in the conditions of high glucose and lipids, which has been widely used to mimic the metabolic disorder that occurs in type 2 diabetic mellitus, and further to verify the role of PGC-1α and SIRT1, cellular energy metabolism regulators, in the process of senescence of EPCs with these combined stimuli. Circulating EPCs were incubated in absence or presence of high glucose (25 mM), FFA (200 µM) or both. EPCs sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Furthermore, the results of an in vivo study indicated that RSV increases SIRT1 expression and stimulates PGC-1a activity in skeletal muscle (24). The results of the present study demonstrate that RSV is able to mitigate the STZ-induced inhibition of SIRT1, PGC-1α and FOXO3a, which is in accordance with previous results (25)(26)(27). A number of previous studies have reported that INS resistance is associated with mitochondrial dysfunction (22) and these results may be caused by oxidative stress (28).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of an in vivo study indicated that RSV increases SIRT1 expression and stimulates PGC-1a activity in skeletal muscle (24). The results of the present study demonstrate that RSV is able to mitigate the STZ-induced inhibition of SIRT1, PGC-1α and FOXO3a, which is in accordance with previous results (25)(26)(27). A number of previous studies have reported that INS resistance is associated with mitochondrial dysfunction (22) and these results may be caused by oxidative stress (28).…”
Section: Discussionsupporting
confidence: 92%
“…2 There are complex pathways involved in the mechanisms of vascular calcification/aging in diabetes, including HG regulation in both endothelial and VSMC layers. 3,4,7,19 Vascular endothelial dysfunction is associated with diabetic conditions, 6,7,20 while little is known about the mechanisms driving calcification/senescence of VSMCs under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The mechanisms underlying vascular calcification/aging in diabetes are complex and multifactorial and include high glucose (HG) regulation at the endothelial level. [5][6][7] However, few findings have been reported supporting the hypothesis that HG alters calcification/senescence of vascular smooth muscle cells (VSMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, diabetic artery calcification/aging leads to arteriosclerosis, amputations, kidney failure, stroke, and increased incidence of cardiovascular events and mortality [3, 4]. Hyperglycemia is the main characteristic of diabetes and increasing evidence has demonstrated that high glucose is an important regulator of endothelial cell senescence, wherein accumulative premature senescent cells participate in the onset and progress of diabetic vascular aging [5, 6]. However, very few reports have studied the effect of high glucose on calcification/senescence of vascular smooth muscle cells (VSMCs).…”
Section: Introductionmentioning
confidence: 99%